Recent Subthreshold Design Techniques - Mohsen Radfar; Kriyang Shah; Jugdutt Singh (Active and Passive Electronic Components)
Considering the variety of studies that have been reported in low-power designing era, the subthreshold design trend in Very Large Scale Integrated (VLSI) circuits has experienced a significant development in recent years. Growing need for the lowest power consumption has been the primary motivation for increase in research in this area although other goals, such as lowest energy delay production, have also been achieved through sub-threshold design. There are, however, few extensive studies that provide a comprehensive design insight to catch up with the rapid pace and large-scale implementations of sub-threshold digital design methodology. This paper presents a complete review of recent studies in this field and explores all aspects of sub-threshold design methodology. Moreover, near-threshold design and low-power pipelining are also considered to provide a general review of sub-threshold applications. At the end, a discussion about future directions in ultralow-power design is also included.